2012
DOI: 10.1002/hep.25834
|View full text |Cite
|
Sign up to set email alerts
|

Variant 1 of KIAA0101, overexpressed in hepatocellular carcinoma, prevents doxorubicin-induced apoptosis by inhibiting p53 activation

Abstract: KIAA0101 overexpression was detected in numerous malignant solid tumors and involved in tumor progression; however, the correlation between KIAA0101 expression level and human hepatocellular carcinoma (HCC) was controversial. Our data revealed abnormal expression of the KIAA0101 transcript variant 1 (KIAA0101 tv1) at both messenger RNA and protein levels in HCC tissues and cell lines assessed by semiquantitative reverse‐transcription polymerase chain reaction (RT‐PCR), virtual northern blot, western blot, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
75
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 37 publications
6
75
1
Order By: Relevance
“…Moreover, we proved that NS5ATP9 prevented LX-2 cells from proliferation and migration, and promoted apoptosis, which differs entirely from its proliferative and anti-apoptotic activities in most types of tumor cells [10,14,28,29], but is consistent with that in others, including HCC [30,31]. The promotion/suppression effects of NS5ATP9 on HSC apoptosis/proliferation may be one of the ways to protect HSCs from maintaining the activation status.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Moreover, we proved that NS5ATP9 prevented LX-2 cells from proliferation and migration, and promoted apoptosis, which differs entirely from its proliferative and anti-apoptotic activities in most types of tumor cells [10,14,28,29], but is consistent with that in others, including HCC [30,31]. The promotion/suppression effects of NS5ATP9 on HSC apoptosis/proliferation may be one of the ways to protect HSCs from maintaining the activation status.…”
Section: Discussionsupporting
confidence: 69%
“…transactivated by the hepatitis C virus (HCV) NS5A protein via the suppression subtractive hybridization technique by our group [8]. NS5ATP9 expression was significantly altered in numerous malignant tumors, including pancreatic cancer, colorectal adenoma and adenocarcinoma, nonsmall cell lung cancer, anaplastic thyroid carcinoma, and liver cancer [9][10][11][12][13]. NS5ATP9 is also involved in the regulation of DNA repair, apoptosis, cellular signaling pathway, cell cycle progression, and cell proliferation [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a previous study showed that overexpression of KIAA0101 greatly decreased the effect of cisplatin plus doxorubicin in hepatocellular carcinoma. 24 Although we did not further explore the underlying molecular mechanisms, this result may provide a novel insight into KIAA0101 for the selection of optimal chemotherapy for EC patients. A further study will pursue such underlying mechanism for effective control of EC.…”
Section: Discussionmentioning
confidence: 92%
“…p15 functions by interacting with PCNA (3032), and its overexpression correlates with poor prognosis in several types of cancer (3336). The study used complementary biophysical techniques to determine the structural details of the PCNA–p15 recognition and the flexibility of the non-interacting regions of p15 (27).…”
Section: Introductionmentioning
confidence: 99%